Structural studies of gangliosides from the YAC-1 mouse lymphoma cell line by immunological detection and fast atom bombardment mass spectrometry - Müthing, Johannes; Peter-Katalinić, Jasna; Hanisch, Franz-Georg; Neumann, Ulrich (Glycoconjugate journal, 1991)
YAC-1 cells were propagated in bioreactors in 1 l and 7.5 l volumes. The cells were metabolically labelled with D-[1-14C]galactose and D-[1-14C]glucosamine. The ganglioside fraction, purified by DEAE-Sepharose and silica gel column chromatography, showed on thin layer chromatography four major bands with mobilities between GM1 and GD1a. Gangliosides, obtained by further purification steps including high performance liquid chromatography on silica gel 60 columns with a gradient system of isopropanol:hexane:water, and preparative high performance TLC were characterized by (1) immunostaining of corresponding asialogangliosides obtained by mild acid hydrolysis and neuraminidase treatment and (2) fast atom bombardment mass spectrometry of native and permethylated samples and methylation analysis of GM1b ganglioside. As well as small amounts of GM2 and GM1, the major gangliosides found in the complex mixture were GM1b and GalNAc-GM1b. The structural heterogeneity of these gangliosides was caused by (a) substitution of the ceramide moiety by fatty acids of different chain length and degree of unsaturation (C16:0, C24:0, C24:1) and (b) N-substitution of the sialic acid moieties with either acetyl or glycolyl groups. Disialogangliosides were detected only in low amounts and will be the subject of further investigation. A polyclonal chicken antiserum was raised against IVNeuAc-GgOse5Cer. The antiserum was highly specific for gangliosides (IVNeuAc and IVNeuGc) and asialogangliosides with a GgOse5Cer backbone. No cross-reaction with GM1b or GgOse4Cer was observed.